ABSENCE OF PALMARIS LONGUS AND PSOAS MINOR MUSCLE – A CASE STUDY - Kulkarni Swarup Purushottam; Patil Sumit Raosaheb; Kalawade Vedashree Abhijit (International Journal of Applied Ayurved Research, 2017)
Palmaris longus and Psoas minor muscles are often considered as vestigial muscles in the human body. Palmaris longus is the muscle of upper extremity present in the flexor compartment of the forearm. Psoas minor is the muscle of the posterior abdominal wall. During the dissection of the male cadaver, we found absence of palmaris longus muscle in the left forearm and also psoas minor muscle was absent in the posterior abdominal wall. The other muscles in the forearm were normally located. The arrangement of the other three muscles in the posterior abdominal wall was also normal. The palmaris longus and psoas minor are having less functional importance. There may not be any functional deformity of the upper extremity and the trunk. Palmaris longus is the weak flexor of the wrist and Psoas minor is considered as weak flexor of the trunk. These muscles are inconstant muscles due to its percentage of absence in the human beings. When the palmaris longus muscle is present, its long tendon can be used for the tendon graft surgeries. When psoas minor muscle is present, it also ends in long and flat tendon and it lies anterior to the psoas major muscle entirely within the abdomen. So this is the attempt to throw the light on the information of these muscles.